Security for telecommunications network management - Rozenblit, Moshe ([S.l.] : Wiley-IEEE Press, 1999)
"Meet the challenge of protecting your telecommunications network management system with SECURITY FOR TELECOMMUNICATIONS NETWORK MANAGEMENT. Leading expert Moshe Rozenblit explains pertinent security-related features to use in your products and offers practical solutions to enable you to plan, implement, and manage the evolution of your network security mechanisms and to better manage security components from several suppliers to ensure overall security of your network management. This book provides a comprehensive discussion of security for telecommunications network management including these featured topics: * Overview of network management for security professionals * Introduction to security mechanisms for network managers * A complete account of OSI-based security management * In-depth analysis of security operations for telecommunications networks * Insights into how to integrate security of network management, management of security-related information, and network operations * The latest security for all standard protocols used in network management: CMIP, CORBA, EDI, and SNMP * Astute comparison of security options and their tradeoffs. SECURITY FOR TELECOMMUNICATIONS NETWORK MANAGEMENT is intended to assist network architects, operations planners, system designers, software engineers, and operation systems developers in understanding and addressing the security implications of the telecommunications network (TMN) in the telecommunications industry, as well as in finance, large manufacturing, military, and government environments."